2004
DOI: 10.1097/01.wcb.0000126565.27130.79
|View full text |Cite
|
Sign up to set email alerts
|

The Upregulation of Cognate and Inducible Heat Shock Proteins in the Anoxic Turtle Brain

Abstract: Summary:Because heat shock proteins (HSPs) have an important protective function against ischemia/anoxia in mammalian brain, the authors investigated the expression of Hsp72 and Hsc73 in the anoxia-surviving turtle brain. Unlike the mammalian brain, high levels of Hsp72 were found in the normoxic turtle brain. Hsp72 levels were significantly increased by 4 hours of anoxia, remained constant until 8 hours, and then decreased to baseline at 12 hours. By contrast, Hsc73 was progressively increased throughout 12 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 11 publications
4
49
0
1
Order By: Relevance
“…It was recently reported that weeks of hypoxic submergence did not alter JNK expression in the cortex of the similarly anoxia-tolerant turtle C. picta, although ERK activation was significantly increased after 5 h hypoxia (Haddad, 2007a, b). Anoxia versus submergence can result in different responses, as has been previously noted, for example, in the expression and upregulation of heat shock proteins (Prentice et al, 2004). Other studies also differ in being cold-temperature submergence studies, where an attempt was made to replicate the turtle's natural overwintering strategy of underwater hibernation, which results in hypoxic or anoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that weeks of hypoxic submergence did not alter JNK expression in the cortex of the similarly anoxia-tolerant turtle C. picta, although ERK activation was significantly increased after 5 h hypoxia (Haddad, 2007a, b). Anoxia versus submergence can result in different responses, as has been previously noted, for example, in the expression and upregulation of heat shock proteins (Prentice et al, 2004). Other studies also differ in being cold-temperature submergence studies, where an attempt was made to replicate the turtle's natural overwintering strategy of underwater hibernation, which results in hypoxic or anoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To decrease neuronal energy requirements, Trachemys decreases membrane ion permeability (''channel arrest''), inhibits the release of excitatory neurotransmitters such as dopamine [10] and glutamate [11], increases the release of inhibitory compounds including adenosine [12] and GABA [13], and decreases electrical activity [14]. In terms of molecular changes, organ-level alterations of MAP kinases, ERK, and JNK have been reported [15], while work in our lab has shown increased expression of heat shock proteins [16] and the downregulation of Kv channel transcription [17]; alterations in many of these molecular factors have been linked to hypoxic/ischemic survival in the mammalian CNS. Such extended anoxic survival time is not a matter of ectothermy, as other reptiles survive only 20-30 min without oxygen [18] and do not exhibit the same neurological adaptations that permit true anoxic tolerance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive levels of mitochondrial Hsp60 were higher in the heart of anoxia-tolerant painted turtles compared with anoxia-intolerant softshell turtles, rabbits, and rats. 54 High constitutive levels of inducible Hsp70 also occur in turtle brain 55 although this protein is typically thought of as being absent or in very low levels in unstressed organisms. High constitutive expression of HSPs could provide turtle organs with a well-developed innate level of protection against protein denaturation that can be called into play whenever anoxia exposure occurs.…”
Section: Hsps In Anaerobiosismentioning
confidence: 99%
“…[55][56][57][58] Figure 2 summarizes HSP responses to 20 hours of anoxic submergence and 5 hours of aerobic recovery in the white muscle of red-eared slider turtles (Trachemys scripta elegans). Anoxia induced a strong 2-to 3-fold increase in protein levels of Hsp25, Hsp40, Hsp70, Hsc70, and Hsp90 in muscle.…”
Section: Hsps In Anaerobiosismentioning
confidence: 99%